2020
DOI: 10.3389/fphys.2020.543331
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β Induced Cytokine Expression by Spinal Astrocytes Can Play a Role in the Maintenance of Chronic Inflammatory Pain

Abstract: It is now widely accepted that the glial cells of the central nervous system (CNS) are key players in many processes, especially when they are activated via neuron-glia or glia-glia interactions. In turn, many of the glia-derived pro-inflammatory cytokines contribute to central sensitization during inflammation or nerve injury-evoked pathological pain conditions. The prototype of pro-inflammatory cytokines is interleukin-1beta (IL-1β) which has widespread functions in inflammatory processes. Our earlier findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 64 publications
(68 reference statements)
0
33
0
1
Order By: Relevance
“…IL-6 powerfully stimulating the activation of the JAK/STAT3 pathway to promote tumor proliferation, motility, and invasion ( Yoon et al, 2012 ). IL-1β induced significant upregulation of pro-inflammatory cytokines in astrocytic ( Gajtko et al, 2020 ). TNF-α is a major factor involved in inflammation-associated cancer and plays an important role in the spread and invasion of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 powerfully stimulating the activation of the JAK/STAT3 pathway to promote tumor proliferation, motility, and invasion ( Yoon et al, 2012 ). IL-1β induced significant upregulation of pro-inflammatory cytokines in astrocytic ( Gajtko et al, 2020 ). TNF-α is a major factor involved in inflammation-associated cancer and plays an important role in the spread and invasion of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal astrocytes are the main source of the IL‐1β which, in turn, acts on its neuronal and astrocytic IL‐1 receptor (IL‐1R) leading to enhanced activation of the local cells (neurons and glia as well) and can lead to the prolonged maintenance of chronic pain 49 . Despite CX3CR1 is mainly expressed by activated microglia, spinal activated‐astrocytes also express CX3CR1 following injury, 50 consistent with our results that CX3CR1 was increased in cultured astrocytes by HATs following CGRP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, intrathecal injection of CGRP and CCI resulted in a tremendous increase in the number of astrocytes with H3K9ac expression. Given that astrocytic activation induced by CGRP, as evident by an increased GFAP expression, was found at the same time, it is conceivable that the increased expression of H3K9ac in astrocytes contributes importantly to the astrocytic activation and its production of inflammatory mediators, 49 , 50 which ultimately brings about neuroinflammation in the spinal dorsal horn. In line with our results, recent studies have indicated that several pro‐inflammatory cytokines and chemokines (IL‐1, CXCL12/CXCR4, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 and PGE-2 are crucial pain factors. Meanwhile,IL-1β can modulate neuronal intracellular calcium signaling and activates astrocytes ,which can further enhance and prolong neuroin ammation-induced chronic pain [25]. IL-17 can promote astrocyte proliferation and proin ammatory cytokines secretion ,which are related to the neuropathic pain [26].…”
Section: Discussionmentioning
confidence: 99%